2019
DOI: 10.1002/hed.26010
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic capacity of Systemic Inflammation Response Index (SIRI) in patients with head and neck squamous cell carcinoma

Abstract: Background: Inflammation and immune evasion are associated with carcinogenesis. Systemic Inflammation Response Index (SIRI) has been proposed as a pretreatment peripheral blood biomarker. The aim of this study is to analyze its prognostic capacity in head and neck squamous cell carcinomas (HNSCC). Methods: We performed a retrospective study in 824 patients with HNSCC. SIRI was calculated by neutrophils*monocytes/lymphocytes. Using a recursivepartitioning analysis considering disease-specific survival (DSS) as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
52
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 25 publications
3
52
2
Order By: Relevance
“…Qi Q et al ( 30 ) conducted a cohort study of patients with advanced pancreatic carcinoma who received palliative chemotherapy, and found that SIRI≥1.8 had a shorter time to progression (HR: 2.348; 95% CI: 1.559-3.535; p =0.003) and shorter OS (HR: 2.789; 95% CI: 1.897-4.121; p < 0.001). In patients with head and neck squamous cell carcinomas, research showed that compared with SIRI<1.1, patients with SIRI between 1.10 and 2.80 had a 1.92 times higher risk of disease-specific death (95% CI: 1.33‐2.82; p =0.001), and patients with SIRI >2.80 had a 2.89 times higher risk (95% CI: 1.86‐4.42; p =0.0001), SIRI was an independent predictor of disease-specific survival ( 31 ). SIRI was also investigated in patients with NPC.…”
Section: Discussionmentioning
confidence: 99%
“…Qi Q et al ( 30 ) conducted a cohort study of patients with advanced pancreatic carcinoma who received palliative chemotherapy, and found that SIRI≥1.8 had a shorter time to progression (HR: 2.348; 95% CI: 1.559-3.535; p =0.003) and shorter OS (HR: 2.789; 95% CI: 1.897-4.121; p < 0.001). In patients with head and neck squamous cell carcinomas, research showed that compared with SIRI<1.1, patients with SIRI between 1.10 and 2.80 had a 1.92 times higher risk of disease-specific death (95% CI: 1.33‐2.82; p =0.001), and patients with SIRI >2.80 had a 2.89 times higher risk (95% CI: 1.86‐4.42; p =0.0001), SIRI was an independent predictor of disease-specific survival ( 31 ). SIRI was also investigated in patients with NPC.…”
Section: Discussionmentioning
confidence: 99%
“…An elevated NLR indicates systemic inflammation. The inflammatory response associated with cancer plays a key role in clinical outcomes [ 14 , 15 , 16 , 25 ]. Cancer cells recruit and activate leukocytes, and although the precise role of neutrophils within the TME remains controversial, they appear to facilitate tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…Systemically, this inflammatory response is manifested by an increase in circulating neutrophils, monocytes, and platelets. In addition, this state of chronic inflammation reduces the number of T-lymphocytes available, capable of acting against tumor cells [ 14 ]. Thus, the neutrophil-to-lymphocyte ratio (NLR) obtained from the peripheral blood count is used as a marker of the relationship between the inflammatory response and the immune response to cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have found a relationship between commonly used blood‐based parameters and prognosis in patients with head and neck squamous cell carcinomas (HNSCC). Some of these parameters include the neutrophil‐to‐lymphocyte ratio, 1 the systemic inflammation response index (SIRI), based on a combined analysis of the neutrophils, monocytes and lymphocytes count, 2 or the Glasgow prognostic score, that includes the C‐reactive protein level to reflect the systemic inflammation status and the serum albumin level to reflect nutritional status 3 . To have markers with prognostic capacity readily available from a simple peripheral blood test makes them attractive parameters to be used for better individualized risk evaluation.…”
Section: Introductionmentioning
confidence: 99%